2019
DOI: 10.1016/j.ynstr.2019.100174
|View full text |Cite
|
Sign up to set email alerts
|

Early life exposures, neurodevelopmental disorders, and transposable elements

Abstract: Transposable elements make up a much larger portion of the genome than protein-coding genes, yet we know relatively little about their function in the human genome. However, we are beginning to more fully understand their role in brain development, neuroinflammation, and adaptation to environmental insults such as stress. For instance, glucocorticoid receptor activation regulates transposable elements in the brain following acute stress. Early life is a period of substantial brain development during which tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 184 publications
(215 reference statements)
2
42
0
1
Order By: Relevance
“…Furthermore, previous studies have shown that L1 activity is modulated by early life experiences, reflecting on neuronal somatic mosaicism and genomic structural variations of the mouse hippocampus (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, previous studies have shown that L1 activity is modulated by early life experiences, reflecting on neuronal somatic mosaicism and genomic structural variations of the mouse hippocampus (30)(31)(32)(33)(34).…”
Section: Discussionmentioning
confidence: 97%
“…How these early life experiences can modulate at molecular level the brain architecture and, ultimately, child's behavior is still an unsolved issue. Interestingly, it has been recently demonstrated that neuronal genomes are plastic in response to environmental cues; in particular, early maternal care can affect genome structural variations in mouse hippocampus, thus resulting in somatic mosaicism that ultimately generates neuronal diversity with potential effect on behavior (30)(31)(32)(33)(34).…”
Section: Introductionmentioning
confidence: 99%
“…Common developmental milestones have been described in particular during the stages prior to birth in both the human and mouse cortex and hippocampus that might determine the correct assembly and functioning of neural circuits in both species, such as, for example, local and commissural connectivity dynamics. Indeed, in utero functional MRI studies have shown that functional connectivity is established in human already before birth (GA [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38], and particularly synchronicity increases at the transition from the second to the third trimester, with the peak around GA 26-29, mainly due to shortrange intrahemispheric and interhemispheric/commissural connections [75]. Similarly, in mouse cortex around E17.5 commissural axons from neurons of the cingulate cortex begin the process of midline crossing acting as pioneers for neocortical callosal neurons, which begin to cross only 1 day later (E18.5), eventually establishing the first interhemispheric connections [76,77].…”
Section: Discussionmentioning
confidence: 99%
“…L1 activity is finely modulated at the level of its endogenous promoter, where a CpG island demethylation is associated with L1 somatic mobilization in the brain [32]. The deregulation of L1 activity has been described in neuronal models of debilitating neurological diseases as Rett syndrome [32], schizophrenia [33], autism spectrum disorder [34], and bipolar and major depressive disorder [35,36]. Notably, early life experience and maternal deprivation has been reported to drive variability in L1 methylation and copy number variations (CNVs) within the mouse hippocampal neuronal genome of the progeny, influencing their behavior [37].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the differential association that sex and age have with PD [ 2 , 3 ], and immune status [ 12 ], we also tested the association between PD and leukocyte proportions and mdNLR in adjusted models. Finally, using genome-wide methylation data allowed us to infer methylation of repeat elements, which make up a large proportion of the human genome and have been demonstrated to have differential methylation in neurological and psychiatric conditions [ 13 – 15 ].…”
Section: Introductionmentioning
confidence: 99%